2012
DOI: 10.4067/s0718-58392012000100017
|View full text |Cite
|
Sign up to set email alerts
|

Integrated use of Rhizobium leguminosarum, Plant Growth Promoting Rhizobacteria and Enriched Compost for Improving Growth, Nodulation and Yield of Lentil (Lens culinaris Medik.)

Abstract: Maintenance of high bacterial population in the rhizosphere improves the efficiency of these organisms. This high bacterial population can be maintained by the application of enriched compost which supports their growth and activities. Thus integrated use of Rhizobium, plant growth promoting rhizobacteria (PGPR) containing 1-aminocyclopropane-1-carboxylate deaminase (ACC-deaminase) and P-enriched compost (PEC) could be highly effective for promoting growth, nodulation, and yield of lentil (Lens culinaris Medik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…This increase in the availability of plant nutrients may also be explained by the production of organic acids by plant roots and bacteria in the rhizosphere which in turn stimulated the availability of plant nutrients through the biodegradation of FYM. The findings obtained in this study are supported by a number of previous studies (Jilani et al, 2007;Kumar et al, 2011;Iqbal et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…This increase in the availability of plant nutrients may also be explained by the production of organic acids by plant roots and bacteria in the rhizosphere which in turn stimulated the availability of plant nutrients through the biodegradation of FYM. The findings obtained in this study are supported by a number of previous studies (Jilani et al, 2007;Kumar et al, 2011;Iqbal et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The enzyme 1-aminocyclopropane-1 carboxylic acid (ACC) is a pre-requisite for ethylene production, catalyzed by ACC oxidase. Iqbal MA et al [40] reported improved nodule number, nodule dry weight, fresh biomass, grain yield, straw yield, and nitrogen content in grains of lentil as a result of lowering of the ethylene production via inoculation with plant growth promoting strains of Pseudomonas sp. containing ACC deaminase along with R. leguminosarum.…”
Section: Nitrogen Fixationmentioning
confidence: 98%
“…Increase in Fe content of both crops was attributed to the production of siderophores by R. leguminosarum strain PEPV16. When used as mixture, the composite rhizobial inoculant provides multiple benefits to crops in addition to their normal physiological activity of N fixation (Iqbal et al, 2012). And hence, the synergistic effects of rhizobia and other free living PGPR/AM-fungi have been found more effective than single inoculation and massively increases vegetables production largely due to enhanced synthesis of phytohormones and nutrient absorption and mobilization (Reimann et al, 2008;Yu et al, 2012).…”
Section: Rhizobiamentioning
confidence: 99%